2017
DOI: 10.1111/pcn.12611
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association studies of bipolar disorder: A systematic review of recent findings and their clinical implications

Abstract: Recent advances in molecular genetics have enabled assessments of the associations among genetic variants (e.g., single-nucleotide polymorphisms) and susceptibility for complex diseases, including psychiatric disorders. Specifically, genome-wide association studies (GWAS), meta-analyses of the GWAS summary statistics, and mega-analyses (which use raw data, not summary statistics) of GWAS have provided revolutionary results and have identified numerous susceptibility genes or single-nucleotide polymorphisms. By… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(27 citation statements)
references
References 66 publications
0
26
0
1
Order By: Relevance
“…Genome‐wide association studies have shown that several genes, each of the modest effect, were identified as being associated with susceptibility for BD . However, these genetic effects are probabilistic and nonspecific for the identification of endophenotype .…”
Section: Circadian Rhythm Markers In Bdmentioning
confidence: 99%
“…Genome‐wide association studies have shown that several genes, each of the modest effect, were identified as being associated with susceptibility for BD . However, these genetic effects are probabilistic and nonspecific for the identification of endophenotype .…”
Section: Circadian Rhythm Markers In Bdmentioning
confidence: 99%
“…Up to this point, the largest GWAS of schizophrenia and bipolar disorder comprise hundreds of thousands of individuals primarily of European descent (Stahl et al, 2019; Ripke et al, 2014; Zhiqiang et al, 2017). While studies of neuropsychiatric diseases in European and Asian ancestry populations continue to grow, the scarcity of studies in African American populations persists (Ikeda et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, functional magnetic resonance imaging studies have succeeded in connecting phenomena of the mind to that in the brain, which has led to the promising new treatment strategy of neurofeedback . Recent genome‐wide association studies have shown the utility of polygenic risk scores (PRS), and analyses using PRS have confirmed traditional clinical findings, for example, early age at onset in major depression as a risk factor of bipolar disorder . Moreover, development of induced pluripotent cell technology has enabled the analysis of patients’ neurons in vitro for the first time …”
mentioning
confidence: 99%
“…However, such remarkable progress has not yet caused innovation in clinical practice in psychiatry, and daily practice in clinics is mostly similar to that of several decades ago. Paradoxically, the progress of biological research has obscured the boundary of diagnostic categories: The same classes of drugs are effective for different types of diseases and there is an overlap in genetic, neuroimaging, and cellular findings across different mental disorders . This may indicate that current biological studies in psychiatry have not grown out of understanding mental disorders’ symptomatic‐level phenomena.…”
mentioning
confidence: 99%